A School-Based Peer-Led Smoking Prevention Intervention with Extracurricular Activities: The LILT-LdP Cluster Randomized Controlled Trial Design and Study Population. Issue 5 (September 2013) - Bosi, Sandra; Gorini, Giuseppe; Tamelli, Marco; Monti, Claudia; Storani, Simone; Carreras, Giulia; Martini, Andrea; Allara, Elias; Angelini, Paola; Faggiano, Fabrizio
Aims and background: Few school programs are effective in preventing adolescents' tobacco smoking initiation. The "Lega contro i Tumori - Luoghi di Prevenzione" is a cluster randomized controlled trial designed to evaluate a school-based peer-led smoking prevention intervention with extracurricular activities for students aged 14–15 years. This paper presents the study design and the baseline characteristics of the study population. Methods and study design: Twenty secondary schools located in the Reggio Emilia province took part in the study. Five schools were excluded because they already participated in smoking prevention interventions. The schools were randomized to control or intervention arms. The study population consisted of students attending the first grade. Components of the intervention included 1) the out-of-school "Smoking Prevention Tour" (SPT) at the "Luoghi di Prevenzione" Center, a 4-hour (4 sessions) extracurricular activity; 2) the "Smoke-free Schools" intervention, combining a life–skills-based peer-led intervention at school, an in-depth lesson on one of the SPT sessions, and enforcement surveillance of the school antismoking policy. Tobacco use was studied through a questionnaire administered before and 6 months after the intervention. Results: Eleven high schools and 9 vocational secondary schools took part in the study for a total of 2, 476 out of 3, 050 eligible students (81.2%). The proportions of respondents in high schools and vocational secondary schools were 90.9% and 64.5%, respectively (P <0.001). Intervention and control arms showed a different distribution of gender and school type, whereas no difference was observed in any tobacco-use characteristic. Conclusions: This study is one of the few Italian trials to evaluate the effectiveness of a school-based program for preventing smoking initiation.